Rural and remote health the international electronic journal of rural and remote health research, education, practice and policy. - Deakin University ([Geelong, Vic.] : Deakin University, 2001)
Rural and Remote Health is an initiative of the Greater Green Triangle University Department of Rural Health, located in south eastern Australia. It aims to provide an easily accessible, peer-reviewed, international evidence base to inform improvement in health service delivery and health status in rural communities.
Title from title screen (viewed on 14 April, 2023).
Text and graphics.
Mode of access: Internet and World Wide Web at: http://www.rrh.org.au/home/defaultnew.asp
Selected for archiving
Keywords: Rural health -- Periodicals; Rural health -- Study and teaching -- Australia -- Periodicals; Rural health -- Australia -- Periodicals